مشكلات تدريس المفردات في المدرسة الثانوية الحكومية بانجيان باتو سنجكار : دراسةوصفية تحليلية - Eri Ramadona; Aida Fitria; M. Zaky Mubarak Lubis (STAI Darul Quran Payakumbuh, 2021)
The main problem in this research is how the problems of mufradat learning in Madrasah Sanawiyah in Pangian, The purpose in this research is to find out the problematics of mufradat learning and mufradat learning materials in madrasah sanawiyah, pangian country. This research is based on qualitative research. And the method used is descriptive analysis method. Because the research produces analytical data.Data collection with observational analysis between researchers and research subjects. The results are in terms of vocabulary understanding, 70% of students say that learning mufradat is very difficult.